Mycobacterium peregrinum Skin Infection: Case Report - Wachholz, Patrick Alexander [UNESP]; Sette, Christiane Salgado; Do Nascimento, Dejair Caitano; Soares, Cleverson Teixeira; Diório, Suzana Madeira; Masuda, Paula Yoshiko (SAGE Publications, 2016)
Background: Mycobacterium peregrinum is a rapidly growing mycobacterium (RGM) that rarely causes skin infections. The correct identification of the specific RGM infecting the skin will enhance therapeutic success. Objective: To highlight the importance of rapid and precise identification of the Mycobacterium involved in skin infections in order to enhance therapeutic success. Methods: We describe an RGM skin infection in an immunocompetent patient. Results: Classic methods (biochemical tests and culture) of RGM identification are time-consuming, and the histopathological features are not specific. Some molecular methods are reliable but expensive. The PRAhsp-65 is a simple procedure that is helpful in identifying the specific agent of an RGM. Conclusion: Although skin infections caused by M peregrinum are rare, they represent a substantial clinical challenge. Specific and more effective treatment options depend on the development of precise and rapid methods for identifying mycobacterial species.
Keywords: Bacterial skin diseases; Case reports; Mycobacterium peregrinum; Rapidly growing mycobacteria; Skin infection